Determinants of the extent of technological innovation adoption among micro, small, and medium food processing enterprises in Davao region, Philippines - Barroga, Kenneth D.; Rola, Agnes C.; Depositario, Dinah Pura T.; Digal, Larry N.; Pabuayon, Isabelita M. (2019)
Micro, small, and medium food processing enterprises (MSMFEs) need to modernize and adopt technological innovations to stay competitive. Various factors influence MSMFEs? ability to adopt innovations. This study aimed to identify the determinants of the extent of adoption among MSMFEs in Davao Region, Philippines. Data were obtained through a census of MSMFEs in the region assisted by DOST?s Small Enterprises Technology Upgrading Program (SETUP), a government program that enables MSMFEs to adopt technological innovations to boost productivity. The analytical tools used were index construction and ordered logistic regression (LR) for quantitative analysis and case studies for qualitative analysis. The statistical or econometric packages available in R software were used in the estimation process and results generation. The adoption indices ascertained which MSMFEs did not adopt technological innovations and which ones adopted less, moderately, and highly or fully. Results showed that 4% of the MSMFEs did not or failed to adopt technological innovations. On the other hand, 21% of the MSMFEs fully adopted the innovations. The majority of them were in the highly adoptive level. Additionally, the extent of technological innovation adoption (TIA) among MSMFEs was mainly influenced by the sex of the owner, educational attainment, business scale, and type of market. Thus, male owners, those with higher educational attainment, and those who own micro-scale businesses catering to both domestic and export markets are likely to adopt more technological innovations. These findings can contribute to a policy establishing an efficient SETUP implementation strategy at the regional and national levels or developing a new program for MSMFEs. (Author's abstract)
Includes bibliographical references (pages 837-839)
Keywords: Determinant; SME; SETUP; Technological innovation adoption